Korelasi kadar hepcidin dan asupan makanan dengan serum transferrin reseptor dan hemoglobin pada remaja stunted overweight - Mani, La; Fatimah-Muis, Siti; Kartini, Apoina (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2019)
Background: Stunted overweight is associated with mild chronic inflammation. The state of inflammation will increase the expression of hepcidin, which affects the iron status of the body, besides the intake of protein, iron, and vitamin C.Objective: To analyze the correlation of hepcidin levels and food intake (protein, iron, vitamin C) with serum transferrin receptors (sTfR) and hemoglobin in stunted overweight adolescents.Method: The design of research was cross-sectional. The subjects were 64 adolescents stunted overweight aged 15-18 years in four high/vocational schools in the Banyumanik District, Semarang City. Measurement the level of hepcidin and sTfR was using the ELISA method and haemoglobin was using Cyanomethemoglobin method. Data on protein, iron, vitamin C intake was using the SQ-FFQ method. Bivariate analysis was using Pearson and Spearman correlation test then followed by multiple linear regression analysis.Results: The result showed that 89.1% subjects had adequate intake of protein, 54.7% subjects had low intake of vitamin C, 76.6% subjects had low intake of iron. Hepcidin levels in all subjects were 100% normal. There were 7.8% subjects with a low sTfR and 7.8% with a low haemoglobin level. Statistic test showed there was correlation between hepcidin with haemoglobin and sTfR (p1 = 0,010 r1 = -0,319, p2 = 0,001, r2 = 0,569). From food intake, only intake iron was correlated with haemoglobin but not with sTfR. There was significant difference between the mean of haemoglobin and sTfR among girls and boys. Further analysis, showed that only hepcidin was a weak negative determinant for sTfR (R2 = 0,120). The determinant factors for haemoglobin were gender (p=0,001) and hepcidin (p =0,004) with the value of R2 = 0,577.Conclusion: Hepcidin correlated with sTfR and haemoglobin while iron intake only correlated with hemoglobin.